INVESTIGATION PERFORMANCE OF PICO HYDRO WATER PIPE TURBINE - Marwani Marwani; Muhammad Zahri Kadir; Ronny Egetha Putra (Indonesian Journal of Engineering and Science (IJES), 2021)
The flow of water in the pipeline for household needs is a source of energy that can generate electrical energy through Pico hydro turbines or small-power water turbines. The experiment has been conducted on a 10 Watt Pico hydro turbine mounted on a water pipe against changes in water flow discharge. The turbine performance analysis is conducted experimentally (actual) and theoretically (ideal). The analysis results showed the greater the discharge flow, the greater the power generated by the turbine. In tests with a maximum discharge of 8.9 l/min, the actual power of 1.121 Watts, the torque of 0.005 Nm with a rotation speed of 2146.8 rpm and efficiency of 12.59%; while the ideal power is based on Euler turbine equation of 4.2 Watts and torque of 0.016 Nm. So, the maximum turbine power that can be generated is only 26.67% ideal. Efficiency turbine decreases with increased discharge; in this test, the maximum efficiency was 24.89% at 5.8 L/min flow discharge.